The threshold and semantic characteristics of fast transient visual-perceptive processes in patients with affective disorders - Shestopalova, Liudmyla F.; Lutsyk, Volodymyr L. (Psychiatry, Neurology and Medical Psychology, 2021)
The article is devoted to the currently topical problem of modern medical psychology, namely the study of conscious and unconscious perceptual-information processes in patients with affective disorders.  The aim of the work was to determine the thresholds and semantic components of visual perception in patients with various forms of affective disorders. The latest method of ultrafast (tachistoscopic) demonstration of visual verbal stimuli was used to examine 23 patients with depression and anxiety-depressive disorders. The obtained results are compared with similar indicants of the control group, which consisted of 15 mentally healthy individuals, and analyzed using Student's criterion, one-way and multifactor models of analysis of variance.  It has been shown that in the presence of an affective disorder, the threshold exposure time required for reliable identification of visual verbal stimuli is on average more than three times higher, i.e. is much worse than a similar perceptual threshold in individuals without mental disorders. Thus, in affective disorders there is inhibition and suppression of not only emotional and psychomotor, but visual-perceptual processes as well. It is proved that the time thresholds of visual perception significantly depend not only on the presence of emotional disorders, but also on their psychopathological structure, as well as on the age factor.  In depressed patients, visual-perceptual disorders are much more pronounced than in patients with anxiety-depressive disorders, namely: in depression, the minimal absolute sensory thresholds are significantly higher, more attempts are made to adapt the visual analyzer, and this deficit is significantly increased depending on age. In patients with depressive and anxiety-depressive disorders also revealed significant features of psychosemantic components of the mechanisms of recognition of verbal stimuli, which consists in a kind of unconscious filtering of the latter with a predominant perception of words with negative emotional loading. The obtained results might be meaningful in the process of developing the new diagnostic methods for affective disorders and in creating the personalized psycho-correctional programs based on the methodological principles of subsensory stimulation.